Enhanced Nitrogen Availability in Karst Ecosystems by Oxalic Acid Release in the Rhizosphere - Pan, Fujing; Liang, Yueming; Zhang, Wei; Zhao, Jie; Wang, Kelin (Frontiers in Plant Science, 2016)
In karst ecosystems, a high level of CaCO3 enhances the stabilization of soil organic matter (SOM) and causes nitrogen (N) and/or phosphorus (P) limitation in plants. Oxalic acid has been suggested to be involved in the nutrient-acquisition strategy of plants because its addition can temporarily relieve nutrient limitation. Therefore, understanding how oxalic acid drives N availability may help support successful vegetation restoration in the karst ecosystems of southwest China. We tested a model suggested by Clarholm et al. (2015) where oxalate reacts with Ca bridges in SOM, thus exposing previously protected areas to enzymatic attacks in a way that releases N for local uptake. We studied the effects of oxalic acid, microbial biomass C (MBC), and β-1,4-N-acetylglucosaminidase (NAG) on potential N mineralization rates in rhizosphere soils of four plant species (two shrubs and two trees) in karst areas. The results showed that rhizosphere soils of shrubs grown on formerly deforested land had significantly lower oxalic acid concentrations and NAG activity than that of trees in a 200-year-old forest. The levels of MBC in rhizosphere soils of shrubs were significantly lower than those of trees in the growing season, but the measure of shrubs and trees were similar in the non-growing season; the potential N mineralization rates showed a reverse pattern. Positive relationships were found among oxalic acid, MBC, NAG activity, and potential N mineralization rates for both shrubs and trees. This indicated that oxalic acid, microbes, and NAG may enhance N availability for acquisition by plants. Path analysis showed that oxalic acid enhanced potential N mineralization rates indirectly through inducing microbes and NAG activities. We found that the exudation of oxalic acid clearly provides an important mechanism that allows plants to enhance nutrient acquisition in karst ecosystems.